Spatiotemporal dynamics of northern Caspian shorelines (1985–2023) and implications for coastal management: Lessons from the Aral Sea - Zihao Duan; Guangsheng Wang; Jielong Hu; Tong Yu; Songgui Chen; Yajing Zhang; Yang Wang; Haicheng Liu; Xu Zhao; Hanbao Chen (PLoS ONE, 2025)
Dynamic changes to the northern Caspian Sea shoreline have significant ecological implications, including impacts to biodiversity and the surrounding environment. This study employs Landsat datasets, historical records, and geographic information systems (GIS) to quantitatively analyze spatiotemporal variations along the northern Caspian Sea coastline from 1985 to 2023. The findings demonstrate pronounced cyclic variations in the Caspian Sea’s water level. Compared to 1930, the water level decreased by 2.6 m by 2023, with 1935 marking the onset of a significant downward trend. From 1995 to 2023, a pronounced decline in the water level at a rate of 6.1 cm/year was observed. Multiscale temporal oscillations in water levels revealed periodic rises and falls with cycles ranging from 6–8 years to 10–16 years. Due to the broad and shallow morphology of the northern Caspian Sea, fluctuations in water level have resulted in significant displacements of the northern coastline. Between 1985 and 2023, the shoreline length decreased by 262 km, which is equivalent to a 17% reduction. The intensity of the coastline length index reached a critical point during from 2010 to 2015, after which it declined sharply by 3.67. By 2023, the coastline had shifted seaward by 1.33 × 10⁴ km2 relative to that in 1985. This continuous retreat of the shoreline poses a severe threat to the ecological stability of the northern Caspian Sea. If the trend persists, then the disappearance of the eastern basin of the South Aral Sea may be replicated in the northern Caspian Sea by 2100. These findings provide critical insights for formulating effective coastal management strategies and conservation initiatives.